DYWIZJA UKRAINSKA I PODOLSKA WOBEC WKROCZENIA ARMII ROSYJSKIEJ DO RZECZYPOSPOLITEJ W 1783 ROKU. (Zaporizhzhia Historical Review, 2021)
The article casts a light upon the activities of Ukrainian Podilska division in times of Russian’s army intervention to Rzeczpospolita in 1783.